2017
DOI: 10.1039/c6dt04533b
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental organometallic chemistry under bimetallic influence: driving β-hydride elimination and diverting migratory insertion at Cu and Ni

Abstract: Bimetallic effects on stoichiometric β-hydride elimination and migratory insertion reactions were examined. Bimetallic reaction conditions drove β-hydride elimination at Cu, while bimetallic C-B elimination occurred in the absence of β-hydrogens. The inherent migratory insertion chemistry of alkynes at Ni was diverted under bimetallic reaction conditions to favor C-H deprotonation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…No evidence was obtained for the known boryl complex, Mn(CO) 5 (Bpin) (bands at 2012.06 and 1959.74 cm À1 ). [76] In order to gain insighti nto the mechanistic process which occurredu nder the reaction conditions used in the development of the synthetic methodology vide supra,t he TR M PS experiments were performed with Mn 2 (CO) 10 in the presence of both PhN 2 BF 4 1c and B 2 pin 2 .W hen the experiment was performed with ac oncentration of Mn 2 (CO) 10 used in the previous experiments, but the ratio of reagents used in Table 1, then [Mn(CO) 3 (NCMe) 3 ] + was the dominant product formed from [Mn(CO) 5 ]C (Figure 3a). Ar elatede xperiment performed at the same concentrationa st he synthetic chemistry showedm ore complicated behavior (Figure 3b)w ith evidencef or the formation of both [Mn(CO) 3 (NCMe) 3 ] + and [Mn(CO) 5 (NCMe)] + .W hile an additional unassigned band at 2071cm À1 was also present in this experiment, these results support the conclusiont hat photochemically generated [Mn(CO) 5 ]C may either act as reducing agent directly or,f ollowing solvent substitution, through [Mn(CO) 3 (NCMe) 3 ]C.I ti sl ikely that subsequent to initiation, the reactionproceeds through ac hain propagation processw hereby trapping of the aryl radicalr esults in the formationo fa boryl radical anion that can reduce another molecule of aryl diazonium 1.…”
Section: Mechanistic Insight Provided By Tr M Psmentioning
confidence: 99%
“…No evidence was obtained for the known boryl complex, Mn(CO) 5 (Bpin) (bands at 2012.06 and 1959.74 cm À1 ). [76] In order to gain insighti nto the mechanistic process which occurredu nder the reaction conditions used in the development of the synthetic methodology vide supra,t he TR M PS experiments were performed with Mn 2 (CO) 10 in the presence of both PhN 2 BF 4 1c and B 2 pin 2 .W hen the experiment was performed with ac oncentration of Mn 2 (CO) 10 used in the previous experiments, but the ratio of reagents used in Table 1, then [Mn(CO) 3 (NCMe) 3 ] + was the dominant product formed from [Mn(CO) 5 ]C (Figure 3a). Ar elatede xperiment performed at the same concentrationa st he synthetic chemistry showedm ore complicated behavior (Figure 3b)w ith evidencef or the formation of both [Mn(CO) 3 (NCMe) 3 ] + and [Mn(CO) 5 (NCMe)] + .W hile an additional unassigned band at 2071cm À1 was also present in this experiment, these results support the conclusiont hat photochemically generated [Mn(CO) 5 ]C may either act as reducing agent directly or,f ollowing solvent substitution, through [Mn(CO) 3 (NCMe) 3 ]C.I ti sl ikely that subsequent to initiation, the reactionproceeds through ac hain propagation processw hereby trapping of the aryl radicalr esults in the formationo fa boryl radical anion that can reduce another molecule of aryl diazonium 1.…”
Section: Mechanistic Insight Provided By Tr M Psmentioning
confidence: 99%
“…Synthesis and investigation of bimetallic systems have recently be considered promising, since they can exhibit unique catalytic [176][177][178][179][180], antiproliferative [181][182][183], and photophysical properties [24,184,185] and attract attention as building blocks for artificial photosynthesis systems [186] owing to the cooperative action of the metals.…”
Section: Reactions With the Formation Of Bimetallic Adducts Retaining The Nhc-m с Bondmentioning
confidence: 99%
“…One foray in this direction has involved the use of Ni(II) pincer complexes. 65 Exposing a (POCOP)Ni-H complex to H-WCp(CO) 3 (HWp) produced the heterobimetallic species (POCOP)NiWp (Scheme 3). This dehydrogenative synthesis was found to be reversible, as exposure of (POCOP)NiWp to H 2 regenerated (POCOP)NiH + HWp.…”
Section: Scheme 2 Stoichiometric Fe-mediated C-h Borylation Under Thermal Conditions 54 and Lack Of Catalytic Turnover Due To Insufficienmentioning
confidence: 99%
“…Indeed, we found that the heterobimetallic complex (POCOP)NiWp is reactive toward acetylenic C-H bonds, generating a nickel(II) acetylide complex along with HWp (Scheme 3). 65…”
Section: Account Syn Lettmentioning
confidence: 99%